2020
DOI: 10.1155/2020/5456707
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of Ag@MOFs Immobilized PVDF Ultrafiltration Membranes with Anti-bacterial and Antifouling Properties

Abstract: In this work, Ag nanoparticle loading Mg(C10H16O4)2(H2O)2(Ag@MOF) composite material was successfully prepared by a facile strategy, and subsequently Ag-MOFs were used to modify the PVDF ultrafiltration membranes to obtain fouling resistance and higher water flux. The as-prepared PVDF membranes were systematically characterized by a series of analytical techniques such as Water Contact Angle (CA), Scanning Electron Microscopy (SEM), and SEM-mapping. Furthermore, the performance of membranes on antibacterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As shown in Table 1, it is seen that the contact angle is reduced with the increment of ZIF‐8 into the PVDF matrix. This is probably due to the presence of hydrophilic NH groups of ZIF‐8 nanocrystals forming a water layer on the surface of PVDF/ZIF‐8 hybrid membranes 48 . Besides, the incorporation of ZIF‐8 nanoparticles into the PVDF dope solution speeds up the coagulation process during membrane fabrication, and thus membranes are formed with a porous structure and a rough surface.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, it is seen that the contact angle is reduced with the increment of ZIF‐8 into the PVDF matrix. This is probably due to the presence of hydrophilic NH groups of ZIF‐8 nanocrystals forming a water layer on the surface of PVDF/ZIF‐8 hybrid membranes 48 . Besides, the incorporation of ZIF‐8 nanoparticles into the PVDF dope solution speeds up the coagulation process during membrane fabrication, and thus membranes are formed with a porous structure and a rough surface.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of AgNPs improves the hydrophilicity of membranes and increases of 36-77% have been reported [55,75,85]. The incorporation of AgNPs into the poly sulphone membranes introduced noticeable changes in morphology and permeate flux, especially in dense mem-branes [86]; however, other studies reported no noticeable morphological changes [55,87]. Table 2 shows how incorporation of AgNPs modifies these surface characteristics and, hence, affects the flux and the fouling propensity.…”
Section: Surface Characteristics Determining Membrane Foulingmentioning
confidence: 99%
“…Table 2 shows how incorporation of AgNPs modifies these surface characteristics and, hence, affects the flux and the fouling propensity. The pure water flux increased from 85 L/m 2 h to 157 L/m 2 h [87] The contact angle decreased from 62.8 • to 54 • for unmodified and Ag-ZnO modified membranes, respectively [89] Surface morphology Nanoparticles uniformly distributed on the surface of the membranes and no significant difference in roughness [55,87] Surface charge…”
Section: Surface Characteristics Determining Membrane Foulingmentioning
confidence: 99%
“…Polymer precipitation occurs because of the solvent and nonsolvent exchange. , The exchange continues until demixing takes place in such a way that the initial homogeneous blending turns into two phases: the polymer-rich phase with embedded MOF particles that gives rise to the membrane structure and the liquid-rich phase that forms the pores. , The internal structure of the final membranes is asymmetric with a dense skin layer and finger-type pores. Several MOFs including ZIF-8, ZIF-L, MIL-53­(Al), MIL-68­(Al), HKUST-1, , HKUST-1@GO, Cu­(tpa)@GO, UiO-NH 2 , UiO-66@GO, MOF-5, Ag-MOF, Ce-MOF, Zn/Co-MOF-74, TMU-5, etc. have been used for functionalization of polymeric membranes for water and wastewater treatment applications.…”
Section: Fabrication Of Mof-functionalized Membranesmentioning
confidence: 99%
“…112,113 The internal structure of the final membranes is asymmetric with a dense skin layer and fingertype pores. Several MOFs including ZIF-8, 114 ZIF-L, 115 MIL-53(Al), 116 MIL-68(Al), 117 HKUST-1, 118,119 HKUST-1@ GO, 120 Cu(tpa)@GO, 121 UiO-NH 2 , 122 UiO-66@GO, 123 MOF-5, 124 Ag-MOF, 125 Ce-MOF, 126 Zn/Co-MOF-74, 127 TMU-5, 128 etc. have been used for functionalization of polymeric membranes for water and wastewater treatment applications.…”
Section: Fabrication Of Mof-functionalizedmentioning
confidence: 99%